2011
DOI: 10.2174/1874471011104040306
|View full text |Cite
|
Sign up to set email alerts
|

Actinium-225 in Targeted Alpha-Particle Therapeutic Applications

Abstract: Alpha particle-emitting isotopes are being investigated in radioimmunotherapeutic applications because of their unparalleled cytotoxicity when targeted to cancer and their relative lack of toxicity towards untargeted normal tissue. Actinium-225 has been developed into potent targeting drug constructs and is in clinical use against acute myelogenous leukemia. The key properties of the alpha particles generated by 225Ac are the following: i) limited range in tissue of a few cell diameters; ii) high linear energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 49 publications
1
123
0
Order By: Relevance
“…71 Like GO and vadastuximab talirine, 225 Ac-lintuzumab ( 225 Ac-HuM195) is an ADC that binds CD33 and is rapidly internalized, liberating the radioisotope 225 Ac, which is retained inside the cell. 72 Frontline studies of 225 Ac-lintuzumab are ongoing, with phase 1 results of an ongoing phase 1/ 2 study showing significant clinical activity with minimal extramedullary toxicity when the ADC was given in combination with LDAC. Because all clinical responses occurred in the first treatment cycle, the authors concluded that LDAC did not contribute to response rates, and phase 2 development of the ADC as a single agent in untreated AML patients who are not candidates for induction chemotherapy is ongoing.…”
Section: Targeted Chemotherapy Deliverymentioning
confidence: 99%
“…71 Like GO and vadastuximab talirine, 225 Ac-lintuzumab ( 225 Ac-HuM195) is an ADC that binds CD33 and is rapidly internalized, liberating the radioisotope 225 Ac, which is retained inside the cell. 72 Frontline studies of 225 Ac-lintuzumab are ongoing, with phase 1 results of an ongoing phase 1/ 2 study showing significant clinical activity with minimal extramedullary toxicity when the ADC was given in combination with LDAC. Because all clinical responses occurred in the first treatment cycle, the authors concluded that LDAC did not contribute to response rates, and phase 2 development of the ADC as a single agent in untreated AML patients who are not candidates for induction chemotherapy is ongoing.…”
Section: Targeted Chemotherapy Deliverymentioning
confidence: 99%
“…Only a few are considered useful as therapeutics agents. These include bismuth-213 (generator produced), 20 astatine-211 (cyclotron produced), 21 actinium-225 (generator produced) 22 and thorium-227 (generator produced). 23 These radiolabelled therapeutic agents transported by bio-vectors such as monoclonal antibodies can be utilized in the treatment of a variety of cancers such as lymphomas, leukaemia and melanomas.…”
Section: Radionuclides Targeting Cancermentioning
confidence: 99%
“…The relative biological effectiveness is designed to relate the absorbed dose of the reference radiation (often low-LET delivered acutely) and absorbed dose of the test radiation (in this case high-LET α particles) that are required to cause equal biological effect (18): either a same surviving fraction of cells for cellular in vitro studies or a same measure of toxicity or therapeutic efficacy in organs or tumors, respectively. The basic equation that defines this concept is: (3) This principle is illustrated in Fig. 1, where a same given surviving fraction of cells from the same cell line is obtained after delivery of an absorbed dose from either a high-LET radiation such as an α particle (D H ) or a low-LET radiation (D L ), given as a single fraction.…”
Section: Conventional Definition Of Relative Biological Effectivenessmentioning
confidence: 99%
“…Advances in the targeted delivery of radionuclides and radionuclide conjugation chemistry, and the increased availability of alpha emitters appropriate for clinical use, have recently led to a resurgence of preclinical studies and a number of clinical trials using radiopharmaceuticals labeled with these radionuclides (1)(2)(3)(4)(5). The same characteristics that make these radiopharmaceuticals attractive for targeting disseminated disease, namely the high-linear energy transfer (LET) and short range (<80 ÎŒm in water) of the α particles, also render their dosimetry complex.…”
Section: Introductionmentioning
confidence: 99%